1991
DOI: 10.3354/meps070105
|View full text |Cite
|
Sign up to set email alerts
|

Growth, otolith growth and RNA/DNA ratios of larval plaice Pleuronectes platessa in the North Sea 1987 to 1989

Abstract: Somatic growth, otolith growth and RNNDNA ratios of larval plaice were studied in the southern North Sea during the years 1987 to 1989. Somatic growth rates were strongly correlated with seawater temperature. Both otolith growth and RNAIDNA ratios were correlated with somatic growth. Age at metamorphosis declined with increasing temperature, but there was no relationshp between size at metamorphosis and temperature. Development seemed to be more related to temperature than to size. Large between-year differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 23 publications
5
66
0
Order By: Relevance
“…Several studies have demonstrated that it is possible to estimate the growth rate by measuring increment widths (Hovenkamp and Witte, 1991;Stunz et al, 2002). Key assumptions for these uses are that the distance between increments is proportional to the somatic growth rate and that increments occur daily (Campana and Neilson, 1985), which were verified for this study.…”
Section: Use Of Growth Indicatorsmentioning
confidence: 86%
See 1 more Smart Citation
“…Several studies have demonstrated that it is possible to estimate the growth rate by measuring increment widths (Hovenkamp and Witte, 1991;Stunz et al, 2002). Key assumptions for these uses are that the distance between increments is proportional to the somatic growth rate and that increments occur daily (Campana and Neilson, 1985), which were verified for this study.…”
Section: Use Of Growth Indicatorsmentioning
confidence: 86%
“…Hovenkamp and Witte (1991) advise using the residuals derived from the logged increment width/otolith radius relationship to compare different growth patterns. As explained above, we standardised all measurements of increment widths to the ten marginal daily increments.…”
Section: Daily Increment Width -Otolith Size Relationshipmentioning
confidence: 99%
“…Mosegaard et al (1988) found a decoupling between somatic growth and otolith growth rates at hyperoptimal temperatures and suggested that metabolic activity, not necessarily somatic growth rate, governs otolith growth rate. Observations showing the relationship between growth rates over the last 5 days (as determined from the width of daily otolith increments) and protein growth rates based on nucleic acid determinations have been described by Hovenkamp (1990), Hovenkamp and Witte (1991) and Clemmesen and Doan (1996) and the results showed that the reaction of the otolith growth and somatic growth is coupled and allows one to determine whether the larval condition is improving or deteriorating. Mugiya and Oka (1991) compared variations in calcium deposition in otoliths and RNA/DNA ratios in muscle of adult rainbow trout (Oncorhynchus mykiss), and showed positive relationships through several days after starvation and during dial experiments.…”
Section: Otolith Microstructure Analysismentioning
confidence: 99%
“…The relationship between RNA and DNA is an index of the cell's metabolic intensity and has been used to measure recent growth in fish (Bulow, 1987;Buckley and Lough, 1987;Hovenkamp, 1990;Hovenkamp and Witte, 1991) and the nutritional condition in larval fish studies (Buckley, 1980(Buckley, , 1984Martin et al, 1985;Fukuda et al, 1986;Buckley and Lough, 1987;Raae et al, 1988;Robinson and Ware, 1988;Clemmesen, 1994;Chícharo, 1997Chícharo, , 1998Kimura et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation